Block Chain Technology to enhance food traceability and safety: case study of Agriculture Industry in Kenya. - Lesiit, Lenjula Letitoiya (Strathmore University, 2020)
Food safety has been one of the growing concerns and challenges in African countries. We had reports of sub standards food stuff, including chemically made eggs being sold to un-suspecting citizens. This is a global challenge, however, it is worth mentioning that it has been a serious issue in Africa due to rampant corruption where the oversight institution are easily compromised by unscrupulous business entities mainly because of lack of tracking system that enable the public know who made decisions or certain approvals. In South Africa, Listeria Outbreak caused 203 fatalities by the time the outbreak was declared over in September 2018. Closer home, Kenya has seen a fair share of food scandal starting with the infamous Aflatoxin-contaminated maize in Kenya resulted in 317 cases of hepatic failure and 125 deaths. There is lack of a system that would ensure companies and individuals involved in production of agricultural produce keep highest level of ethics; through a transparent supply chain management system that not only give the policy makers and oversight organization openness but also neutrality, reliability and thus security of the produce from the farm to table. This projects main objective is to develop a system that will guarantee food quality and safety from supply chain perspective by applying blockchain technology in agricultural supply-chain management, from farm to table. Since its conception in 2008, blockchain has developed over the last decade into one of today’s biggest technologies with a massive potential to impact virtually every industry from financial to manufacturing to educational institutions. Blockchain provided the answer to digital trust because it records important information in a public space and doesn’t allow anyone to remove it; it’s transparent, time-stamped and decentralized. The system developed enhances food safety and integrity through higher traceability thus helping everybody stakeholder in the supply chain quickly trace outbreaks back to specific sources, which could mitigate food fraud or food crises. The stakeholder are not only able to get quality and safer products but also forces the dishonest business entities out of business therefore making the market safe. The system offers many other benefits tandem to the blockchain attributes such as, providing a secure way to perform transactions among untrusted parties; decentralizing ledger that helps in connecting inputs, suppliers, producers and buyers.
A Thesis Proposal Submitted to the Faculty of Information in partial fulfillment of the requirements for the award of Master of Science in Information Technology of Strathmore University.
Keywords: Block Chain Technology; Agriculture Industry; Food Traceability